Integrated photovoltaic and battery energy storage (PV-BES) systems: An analysis of existing financial incentive policies in the US. (15th February 2018) - Zhang, Jian; Cho, Heejin; Luck, Rogelio; Mago, Pedro J.
Highlights: Photovoltaic and Battery Energy Storage (PV-BES) are analyzed. Techno-economic analysis of PV-BES is performed. Payback periods of PV-BES with and without financial incentives are determined. Effectiveness of the existing financial incentives to promote PV-BES is evaluated. Greenhouse gas mitigation is evaluated as an additional indicator. Abstract: This paper presents an analysis of existing financial incentive policies in the U.S. for integrated photovoltaic and battery energy storage (PV-BES) systems. A mathematical model of PV-BES system to evaluate annual energy performance is developed in this paper. Four types of buildings (i.e., hospital, large office, large hotel, and secondary school) located in four different states, which each has their own PV and/or BES incentives, are selected and analyzed. Based on the energy performance data for each building type, the simply payback period (PBP) for the PV-BES system in different locations is calculated according to the local incentive policies. The PBP is chosen as an indicator to evaluate the effectiveness of incentive policies for different locations and building types by comparing it to the PBP for the same PV-BES systems without incentive policies. The reduction of carbon dioxide emission (CDE) due to the PV generation is also investigated since it indicates the potential to reduce the PBP for a further step when a high carbon credit is available. Furthermore, a parametric analysis is conducted to determine the sensitivity and contribution of parameters such as the capacity of the PV-BES system, the capital cost of PV module and the battery storage on the performance of the PV-BES system. Results show that for all the evaluated buildings in California and Hawaii, the existing incentive policy could reduce the PBP effectively below 10 years. However, the PBP for most of the evaluated buildings in New Jersey and New York were high even when both the PV and BES incentive policies were taken into account (approximately from 11 to 29 years).